Zakat sebagai Instrumen Finansial Islami - Ningsih, Siti Warsini; Salsabila, Putri Cinta Ayu; Nurafifah, Rani; Wakhid, Citra Fadilah; Hidayati, Amalia Nuril (Yayasan Rahmat Islamiyah, 2025)
This research aims to analyze the role of zakat as an Islamic financial instrument that not only functions as a spiritual obligation, but also as an effective wealth redistribution mechanism. Using the literature study method, this research examines primary literature such as the Al-Qur'an and Hadith, as well as secondary references in the form of books and scientific journals that discuss aspects of zakat in a modern context. The results of the analysis show that zakat has great potential in overcoming poverty, reducing economic disparities, and encouraging community economic empowerment. In addition, zakat is able to contribute to social stability by increasing economic inclusion and reducing conflict due to social inequality. If optimized, zakat can be an integral solution in sustainable economic development that is in line with the principles of Islamic law. Thus, the role of zakat as an Islamic financial instrument is not only relevant in a spiritual context, but also has a significant impact on social stability, economic empowerment and sustainable development.